Solusi Inovatif Meningkatkan Minat Baca di Era Digital - Nabila Nur Anisah; Anggi Trio Meisya; Paisah; Valencia Nanda Luckyta; Dian Puspita (Jurnal Pustaka Cendekia Pendidikan, 2025)
In the rapidly evolving technological era, reading interest—especially among the younger generation—has significantly declined. This shift is primarily due to changes in habits of accessing information, moving from reading long texts to consuming visual and audio content through social media, short videos, and other digital platforms. This study aims to explore innovative solutions that can be implemented to increase reading interest amidst digitalization. The method used is literature review and observation of technological trends related to reading behavior. The findings reveal that integrating technology such as interactive e-books, gamified digital literacy apps, virtual reading communities, and the use of social media for literacy content can effectively reignite reading interest. These solutions must be aligned with the preferences of the digital generation, who favor interactive and visually engaging experiences. Collaboration between educational institutions, app developers, and government bodies is essential to create an adaptive, enjoyable, and sustainable literacy ecosystem in this technological age.